EpCAM Is Essential to Maintaining the Immune Homeostasis of Intestines via Keeping the Expression of pIgR in the Intestinal Epithelium of Mice - Lei, Zili; Liu, Wanwan; Nie, Ya; Yang, Yanhong; Chen, Guibin; Huang, Li; Wu, Huijuan; Lei, Yuting; Chen, Lei; Hu, Qing; Rong, Hedong; Yu, Siping; et al. (Frontiers in Immunology, 2022)
EpCAM deficiency causes congenital tufting enteropathy (CTE) which is considered as one kinds of very early onset inflammatory bowel disease (IBD). However, functions of EpCAM on regulating the immunity of intestines is still unclear. To study the mechanism of EpCAM on maintaining the intestinal immune homeostasis, the intestines of WT and EpCAM-/- mice at E18.5, P0 and P3 stages were collected for morphological, histological and gene expression tests. Serious inflammation was detected in the small intestines of P3 EpCAM-/- mice. Compared to WT mice, genes related to inflammatory factors and immunity cells, including TNFα, IL-1β, IL-6, IL-8rb, MIP2, MCP1, Ly6d and Ly6d, were all significantly upregulated and the expression of intestinal abundance matrix metalloproteinases (MMPs) was also significantly increased in the intestines of EpCAM-/- mice at E18.5, P0 and P3 stages. Signals of p38, ERK1/2 and JNK were hyper-activated in the intestines of EpCAM-/- mice. The expression of pIgR was significantly decreased and the expression and activation of transcriptional factors which promote the expression of pIgR were also reduced in the intestines of EpCAM-/- mice compared to WT controls. In conclusion, EpCAM could maintain the immune homeostasis of intestines via keeping the expression of pIgR in the intestinal epithelium.